Retrosternal hematoma causing torsade de pointes after coronary artery bypass graft surgery; a case report - Sharifkazemi, Mohammadbagher; Ghazinour, Mohammad; Lotfi, Mehrzad; Khorshidi, Soorena; Davarpasand, Tahereh (Frontiers in Cardiovascular Medicine, 2024)
Myocardial infarction is among the top causes of mortality worldwide. Survivors may also experience several complications. Infarct-related torsade de pointes (TdP) is an uncommon complication. In the context of myocardial infarction, coronary artery bypass graft (CABG) surgery is the prevalent therapeutic modality associated with several early and late complications. Ventricular tachyarrhythmias, including TdP, because of electrical inhomogeneity, would potentially be a lethal complication of CABG. Here, we report the occurrence of medically intractable TdP in the presence of an uncommon case of a post-CABG retrosternal hematoma. Arrhythmia was properly resolved after hematoma removal surgically. It showed the possibility of a “cause and effect” relationship between these two complications. This unique case emphasizes the post-CABG medically-resistant TdP, considering the mechanical pressure effect of retrosternal hematoma that stimulates this potentially malignant arrhythmia, especially in the absence of electrolyte disturbances and evident symptoms of ongoing ischemia.